Borderline ovarian tumors: Guidelines from the French national college of obstetricians and gynecologists (CNGOF). (January 2021) - Bourdel, N.; Huchon, C.; Abdel Wahab, C.; Azaïs, H.; Bendifallah, S.; Bolze, P.A.; Brun, J.L.; Canlorbe, G.; Chauvet, P.; Chereau, E.; Courbiere, B.; De La Motte Rouge, T.; et al.
Abstract: It is recommended to classify Borderline Ovarian Tumors (BOTs) according to the WHO classification. Transvaginal and suprapubic ultrasonography are recommended for the analysis of an ovarian mass (Grade A). In case of an undetermined ovarian lesion on ultrasonography, it is recommended to perform a pelvic MRI (Grade A) with a score for malignancy (ADNEX MR/O-RADS) (Grade C) included in the report and to formulate a histological hypothesis (Grade C). Pelvic MRI is recommended to characterize a tumor suspected of being BOT (Grade C). It is recommended to evaluate serum levels of HE4 and CA125 and to use the ROMA score for the diagnosis of indeterminate ovarian mass on imaging (grade A). If there is a suspicion of a mucinous BOT on imaging, serum levels of CA 19−9 may be proposed (Grade C). For Early Stages (ES) of BOT, if surgery without risk of tumor rupture is possible, laparoscopy with protected extraction is recommended over laparotomy (Grade C). For treatment of a bilateral serous ES BOT with a strategy to preserve fertility and/or endocrine function, bilateral cystectomy is recommended where possible (Grade B). For mucinous BOTs with a treatment strategy of fertility and/or endocrine function preservation, unilateral salpingo-oophorectomy is recommended (grade C). For mucinous BOTs treated by initial cystectomy, unilateral salpingo-oophorectomy is recommended (grade C). For serous or mucinous ES BOTs, routine hysterectomy is not recommended (Grade C). For ES BOTs, lymphadenectomy is not recommended (Grade C). For ES BOTs, appendectomy is recommended only in case of a macroscopically pathological appendix (Grade C). Restaging surgery is recommended in cases of serous BOTs with micropapillary architecture and an incomplete abdominal cavity inspection during initial surgery (Grade C). Restaging surgery is recommended for mucinous BOTs after initial cystectomy or in cases where the appendix was not examined (Grade C). If restaging surgery is decided for ES BOTs, the following procedures should be performed: peritoneal washing (grade C), omentectomy (grade B), complete exploration of the abdominal cavity with peritoneal biopsies (grade C), visualization of the appendix and appendectomy in case of a pathological macroscopic appearance (grade C) as well as unilateral salpingo-oophorectomy in case of a mucinous BOT initially treated by cystectomy (grade C). In advanced stages (AS) of BOT, it is not recommended to perform a lymphadenectomy as a routine procedure (Grade C). For AS BOT in a patient with a desire to fall pregnant, conservative treatment involving preservation of the uterus and all or part of the ovary may be proposed (Grade C). Restaging surgery aimed at removing all lesions, not performed initially, is recommended for AS BOTs (Grade C). After treatment, follow-up for a duration greater than 5 years is recommended due to the median recurrence time of BOTs (Grade B). It is recommended that a systematic clinical examination be carried out during follow-up of a treated BOT (Grade B). If the determination of tumor markers is normal preoperatively, the routine dosage of tumor markers in BOT follow-up is not recommended (Grade C). In case of an initial elevation in serum CA 125 levels, it is recommended to monitor CA 125 during follow up (Grade B). In case of conservative treatment, it is recommended to use transvaginal and transabdominal ultrasound during follow up of a treated BOT (Grade B). In the event of a BOT recurrence in a woman of childbearing age, a second conservative treatment may be proposed (Grade C). A consultation with a physician specialized in Assisted Reproductive Technique (ART) should be offered in the case of BOTs in women of childbearing age (Grade C). When possible, a conservative surgical strategy is recommended to preserve fertility in women of childbearing age (Grade C). In the case of optimally treated BOT, there is no evidence to contraindicate the use of ART. The use of hormonal contraception after serous or mucinous BOT is not contraindicated (Grade C). After management of mucinous BOT, for women under 45 years, given the benefit of Hormonal Replacement Therapy (HRT) on cardiovascular and bone risks, and the lack of hormone sensitivity of mucinous BOTs, it is recommended to offer HRT (Grade C). Over 45 years of age, HRT can be prescribed in case of a climacteric syndrome after individual benefit to risk assessment (Grade C).